2013
DOI: 10.1371/journal.pone.0081148
|View full text |Cite
|
Sign up to set email alerts
|

A Reference Methylome Database and Analysis Pipeline to Facilitate Integrative and Comparative Epigenomics

Abstract: DNA methylation is implicated in a surprising diversity of regulatory, evolutionary processes and diseases in eukaryotes. The introduction of whole-genome bisulfite sequencing has enabled the study of DNA methylation at a single-base resolution, revealing many new aspects of DNA methylation and highlighting the usefulness of methylome data in understanding a variety of genomic phenomena. As the number of publicly available whole-genome bisulfite sequencing studies reaches into the hundreds, reliable and conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
322
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(340 citation statements)
references
References 42 publications
3
322
0
Order By: Relevance
“…Six of the additional CpG islands were included as negative or methodological controls, while a CpG island at DLX5 was included for a secondary hypothesis (see below). Although we could not control our data for possibly relevant variables such as medication use or white cell concentration in blood, the profiles of methylation obtained for all of these targets corresponded well with those reported in publicly available datasets derived from blood DNA (supplementary data S4) [Lister et al, 2009;Heyn et al, 2012;Song et al, 2013;Li et al, 2010;Gertz et al, 2011;Hodges et al, 2011]. We found that methylation at the LRRTM1 promoter was decreased in sibling pairs affected with psychosis.…”
Section: Brucato Et Al 559supporting
confidence: 63%
See 1 more Smart Citation
“…Six of the additional CpG islands were included as negative or methodological controls, while a CpG island at DLX5 was included for a secondary hypothesis (see below). Although we could not control our data for possibly relevant variables such as medication use or white cell concentration in blood, the profiles of methylation obtained for all of these targets corresponded well with those reported in publicly available datasets derived from blood DNA (supplementary data S4) [Lister et al, 2009;Heyn et al, 2012;Song et al, 2013;Li et al, 2010;Gertz et al, 2011;Hodges et al, 2011]. We found that methylation at the LRRTM1 promoter was decreased in sibling pairs affected with psychosis.…”
Section: Brucato Et Al 559supporting
confidence: 63%
“…This served as a useful validation of our method for quantifying methylation. The six other genes showed profiles of methylation comparable to those recorded in publicly available epigenomic datasets in which whole blood DNA was analyzed (supplementary data S4) [Lister et al, 2009;Heyn et al, 2012;Song et al, 2013;Li et al, 2010;Gertz et al, 2011]. The LRRTM1 promoter showed generally low levels of methylation while also showing inter-subject variation (Table I).…”
Section: Methylation Levelsmentioning
confidence: 60%
“…Normally methylated regions with a minimum size of 200 bp were determined using the RSEG software package (smithlabresearch.org/software/rseg/). To display the bisulfite sequencing data, the average 5mC level was determined for specified step-wise window sizes across the genome using the MethPipe program (smithlabresearch.org/software/methpipe/) (43). The resulting file was renamed with an .igv file extension to allow display on the Integrated Genome Viewer (software.broadinstitute.org/software/igv/) (44).…”
mentioning
confidence: 99%
“…This assumes 100 Gb raw data on the 2500 and 4000 at list prices (currently $32.60 and $30.24 per Gb respectively), and 120 Gb on the HiSeq X to account for the additional spike-in needed, as well as the elevated platform-specific duplicate 15 rates. Library preparation costs for X-WGBS are similar to standard commercial kits.…”
Section: Figurementioning
confidence: 99%
“…We used 50,000 cells from two biological replicates of GM12878, harvested during the exponential growth phase. The cells were spun at 500 g for 5 minutes at 4˚C and then 15 washed using 50 μL of cold 1X PBS. Samples were then centrifuged at 500 g for 5 minutes.…”
Section: Atac-seq Library Preparationmentioning
confidence: 99%